CREATIVE PEDAGOGY TRAINING FOR SCHOOL COUNSELORS: STRATEGIES TO FOSTER JOYFUL AND MEANINGFUL LEARNING IN GUIDANCE AND COUNSELING SERVICES - Susi Fitri; Mohamad Saripudin; Irsyad Ridho; Carol Carter; Paul Gardner (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2025)
Kompetensi professional konselor sekolah dalam penyelenggaraan layanan bimbingan dan konseling disekolah membutuhkan peningkatan. Untuk mengatasi permasalahan lemahnya kompetensi professional konselor sekolah, perlu dilakukan program pelatihan yang ekstensif. Program pengabdian masyarakat ini bertujuan untuk mengembangkan komptensi professional konselor khususnya memperkaya metode penyelenggaraan layanan bimbingan dan konseling melalui pedegogi kreatif. Pengabdian kepada masyarakat ini masuk dalam jenis kolaborasi internasional antara Universitas Negeri Jakarta dengan Curtin University. Metode yang digunakan terdiri dari socialization, training, mentoring, make learning video, evaluation and follow up. Pelaksanaan sosialisasi dilakukan penyebaran browsurmelalui WhatsApp Group. Pelatihan dilakukan selama dua hari yaitu pada tanggal 27 dan 28 Mei 2025. Mentoringdilakukan selama dua sesi yang dilakukan secara daring. Evaluasi dilakukan selama proses dan hasil pelatihan. Followup yaitu pengembangan program lain untuk mengembangkan kompetensi konselor bersama ABKIN Jakarta dan pengembangan buku yang berisi kumpulan RPP/RPL dari hasil pelatihan. Abstract The professional competence of school counselors in providing guidance and counseling services in schools needsto be improved. An extensive training program is needed toovercome the problem of weak professional competence ofschool counselors. This community service program aims todevelop the professional competence of counselors, especiallyenriching the methods of providing guidance and counselingservices through creative pedagogy. This community serviceis included in the type of international collaboration betweenJakarta State University and Curtin University. The methodsused consist of socialisation, training, mentoring, making learning videos, evaluation, and follow-up. The implementation of socialisation is carried out by distributingbrochures via a WhatsApp Group. The training was carriedout for two days, namely on May 27 and 28, 2025. Mentoringwas carried out during two sessions, which were conductedonline. Evaluation was carried out during the trainingprocess, and the results were. Follow up is the development ofother programs to develop counselor competence with ABKIN Jakarta and the development of books containing a collectionof RPP/RPL from the results of the training.